Components of variance and interaction between genotype and environment for annual girth increment in rubber tree - Gonçalves, Paulo de Souza (1998)
To determine the nature and extent of genetical and environmental control of vigour through annual girth increment in rubber trees [Hevea brasiliensis (Willd. ex Adr. de Juss.) Müell. Arg.], seven clones were studied in a replicated trial in São Paulo State at four different locations. The clones represented a range of imported germoplasm while the locations were selected to represent a range of rubber growing areas. Trees were studied for annual girth increment over five years before the initiation of tapping for latex. The results of the analyses show a consistent decrease in genetic component over the five years from 10 per cent to 0.5 per cent with a corresponding increase in the effect of environment (19.0 per cent to 93.0 per cent). The genotype x environment effects from combined analysis were significant for three factor analysis of variance. Genetic correlations between locations for annual girth increment revealed a consistent positive and significant correlation between Mococa and Matão in the fifth year (rg= 0.7128), Ribeirão Preto and Matão in the fifth year (rg=0.7113) and Ribeirão Preto and Presidente Prudente in the fourth year (rg=0.9367). The implications of these findings in selection of rubber for annual girth increment trait are discussed.